PENGEMBANGAN BUKU PEMBELAJARAN BAHASA INDONESIA BERMUATAN KESANTUNAN BERBAHASA LINTAS BUDAYA: ANCANGAN PSIKOLINGUISTIK PENDIDIKAN - ., Subyantoro (Universitas Muhammadiyah Surakarta, 2012)
The purpose of this research is to develop the Indonesian coursebooks which contain cross-cultural politeness. The method of the research is Research and Development (R&D). The sources of data are teachers, parents of students, and undergraduate students of elementary school, junior high school, and senior high school in Semarang, Purwokerto, and Sukoharjo. The research instruments of this study are interview, observation, and questionnaire. The results of this study show that: (1) cross-cultural politeness is manifestated in some performative sentences, statements of preference, and the formulation of recommendations in the speech act, (2) the products of this research are: a course book of polite usage of Indonesian language, a handbook of writing polite Indonesian language, and CD of teaching material. The feasibility of the products has been assessed by experts of teaching and ICT.